Analysis of Indication, Surgical Technique and Outcome of Total Laparoscopic Hysterectomy Procedures Performed at Tertiary Hospital of Eastern Nepal - Pandey, Shuvechha; Karki, Gyanendra Man Singh; Das, Tanya (Annapurna Journal of Health Sciences, 2026)
Background: Total Laparoscopic Hysterectomy (TLH) is a preferred minimally invasive alternative to abdominal hysterectomy due to less postoperative pain, shorter hospitalization, faster recovery, and better cosmetic outcomes.This study aimed to evaluate the indications, operative techniques, and perioperative outcomes of TLH in tertiary care settings of Eastern Nepal. Methods: This descriptive cross-sectional study was conducted at a tertiary hospital in Eastern Nepal from February 2024 to February 2025. Data were entered and analyzed using Statistical Package for Social Sciences (SPSS) version 25, and descriptive statistics were used to summarize the findings. Results: A total of 116 patients underwent TLH. Most patients were aged 40–44 years (38.8%) and multiparous (89.7%), with 75% having normal or overweight BMI. The most common indication was symptomatic fibroid uterus (48.3%), followed by chronic pelvic pain (11.2%) and adenomyosis refractory to medical therapy (9.5%). Postoperative outcomes were favorable, with 75% of patients experiencing no complications. Minor complications (Clavien–Dindo grades I–II) occurred in 20.7%, while major complications (grades IIIa–IIIb) were rare (4.3%). Preoperative and postoperative diagnoses showed good concordance, with endometriosis identified in approximately 13% of cases. Conclusions: TLH is a safe and effective minimally invasive procedure with favorable perioperative outcomes in tertiary care settings in Eastern Nepal. Symptomatic fibroid uterus remains the leading indication, and standardized laparoscopic techniques, including direct blunt trocar entry, demonstrate low complication rates. These findings support the expanding role of TLH in routine gynecological practice in resource-constrained settings. Indications, Total Laparoscopic Hysterectomy, Outcomes Surgical Technique